How to solve your own murder : a novel - Perrin, Kristen (Dutton, 2024)
"A dual narrative, feel good mystery in which a woman, Frances, spends a lifetime trying to prevent her murder as predicted by a fortune teller at a country fair when she was just 17. When she is in fact murdered nearly 60 years later, her great niece Annie must solve the crime to avenge her great aunt's death, and in so doing uncovers the dark heart of the quaint English village of Castle Knoll, where she might just find herself in the path of the killer"--